Reproductive biology of terminalia species of tropical moist decidous forests of Kerala - Saju P U (Department of Tree Physiology and Breeding, College of Forestry, 2000)
An investigation was carried out in Kerala Agric~ltural University campus and Vazhachal Forest Division on the reproductive biology of Termina/ia species of tropical moist deciduous forests of Kerala with the objective of understanding the phenology, floral biology, morphology, flowering, self fertilization, pollination time, fruit set and seed matruity of its species. Four species of Termina/ia viz., Terminalia paniculata, T. tomentosa, T. catappa and T. be/erica were observed for a period of twelve months starting from June 1996 to July, 1997. The study revealed that leaf shedding and dormancy occurred in dry months and flushing occurred after the dormant period facilitate the utilization of high moisture available during the rainy season. The inflorescence of T. panicu/ata and T. tomentosa was panickled spikes and in T. catappa and T. be/erica it was simple spike. All flowers were hermaphrodite in T. panicu/ata and T. tomntosa but in T. catappa and T. be/erica the only lowermost six were hermaphrdite and others were male flowers with defective overy. Mass flowering was observed in T. be/erica and T. tomentosa, but steady state type of flowering activity was observed in T. ceteppe and intermediate type of flowering pattern was noticed in T. panicu/ata. The anthesis and antherdehiscence occurred during the morning and evening hours in Termina/ias facilitate high insect activity and maximum pollination. The stigma receptivity was high at the time of anthesis and it declines sharply with its age. The fruit development phases and seed maturity were distinguishable from the colour change of their fruits. The extent of fruit set seed maturity and reproductive capacity of Terminaliassuggested that only very small proportion of the flowers producerd were transformed into viable fruits.